Adabiah Da'wah Strategy Of Indonesian Muslim Youth - Santoso, Bobby Rachman (TASAMUH, 2023)
Da'wah now should focus on youth. Teenagers should convey da'wah and use strategies that are suitable for the condition of society, especially teenagers and changing times. The da'wah strategy that is applied in various activities is followed by the latest communication media that is able to provide the overall appeal of mad'u. The development of modern technology and media has an impact on the da'wah strategies carried out by teenagers, which must be recognized in order to get feasibility and recognition in the world of da'wah. Especially in this day and age people are presented with a wide range of life problems. Teenagers can create adabiah da'wah by staying guided by Islamic teachings. The da'wah strategy carried out can attract public attention and reduce the negative side of the current era. Teenagers are required to understand the situation and condition of mad'u both socially and psychologically to find the right strategy in preaching.